Analisis Kemampuan Pemahaman Konseptual Ditinjau dari Tingkat Kemampuan Siswa dalam Menyelesaikan Soal Literasi Matematika SMP - Yurianti, Syarifah; T, Ahmad Yani; Siregar, Nurfadhilah; Meldi, Nadya Febriani (Universitas Sultan Ageng Tirtayasa, 2025)
This research aims to describe the conceptual understanding ability of class VIII students in solving mathematical literacy problems. This research uses a descriptive qualitative method with the research subjects consisting of 33 students of class VIII of SMP Negeri 3 Tekarang for the 2024/2025 academic year. Data collection techniques were obtained from the results of the validated mathematical conceptual understanding ability test and unstructured interviews. The results of this study indicate that 3 students are in the very high category with a percentage of 9.1%; 9 students are in the high category with a percentage of 27.27%; 5 students are in the medium category with a percentage of 15.15%; 5 students are in the low category with a percentage of 15.15% and 11 students are in the very low category with a percentage of 33.33%. This shows that the students' conceptual understanding ability reaches 48.48% of the 33 students, which is still in the low category, so it has not met the indicators of students' conceptual understanding ability in solving mathematical literacy problems on the material of a system of two-variable linear equations.